Efforts to Enhance Sustainable Consciousness and Critical Thinking in High School Students Through Learning Projects - Purwaningsih, Widi; Arrifa, Filza Huaina; Riandi, R. (Universitas Pendidikan Indonesia (UPI), 2023)
Awareness or Sustainability consciousness (SC) is an essential part of Education For Sustainable Development (ESD) and closely relates to critical thinking skills. Therefore, training and instilling the two things above is a necessary task for teachers in contributing to realizing sustainability Development Goals (SDGs). This research aims to identify the influence of learning project zero waste school on sustainable awareness and students' critical thinking ability. This study uses a Quasi-Experimental method with a Non- Equivalent Control Group Design. The sample consisted of 63 students in the experimental class and 63 students in the control class. In the implementation of learning in the practical class using the model zero waste school project and in the control class using conventional models. Data study collected with the use awareness questionnaire sustainable and test descriptions given before and after learning is done. The research results show that the zero waste school project can influence sustainable awareness and skills. Students' critical thinking is higher than learning given without a project. The results of students' critical thinking are trained through model learning project zero waste school, generally for all indicators showed significantly higher results than the control class. Of the six hands, the indicator that experienced the highest increase was the evaluation indicator, while the indicator that experienced the lowest growth was the interpretation indicator.